BIOSORPTION OF CRYSTAL VIOLET DYE FROM AQUEOUS SOLUTIONS USING NATURAL BIOSORBENTS - Rashmi, A S; Sahithi, P; Rao, P Raja (LIFE: International Journal of Health and Life-Sciences, 2015)
Textile and dyeing industries are continuously increasing the pollution levels of water bodies regularly due to improper treatment and disposal of their effluents. The synthetic dyes are recalcitrant in nature and their intense color leads to the reduction in photosynthesis and raise temperature in the deeper layers of water bodies causing serious damage to the aquatic life. It is necessary to adopt eco-friendly treatment methods like bio sorption and microbial decolorization to decolorize the effluents before they are disposed into the environment. Batch mode bio sorption experiments were carried out using the Annona reticulata leaves powder and Cucurbita maxima seed powder. Optimization studies were carried out for the decolorization of crystal violet dye. Under optimized conditions, the percentage decolorization by bio sorbent, Annona reticulata leaves powder (at pH = 8, temperature 400C) was 90.3% for 60 minutes. The amount of biosorbent dosage added for maximum color removal is 0.2g/ 100ml. In case of Cucurbita maxima seed powder, the percentage removal was 98.5% under same conditions. Effective removal was observed by Cucurbita maxima seed powder compared to Annona reticulata leaves powder. Toxicity assay showed that in the presence of biosorbent Annona reticulata leaves the growth of microbes was more favorable when compared to Cucurbita maxima seed powder. The present study reveals that the use of natural biosorbents in the decolorization of industrial effluents is an effective and commercially viable technique.